2017
DOI: 10.1200/jco.2017.35.15_suppl.1564
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening in transgender patients: Findings from the 2014 BRFSS survey.

Abstract: 1564 Background: Transgender patients undergoing transitions often receive cross sex hormonal therapies, placing them at uncertain risk for developing breast cancer. There is limited population-based information about the extent to which transgender patients undergo mammography screening. Our purpose was to determine the extent to which transgender patients undergo mammography screening using nationally representative survey data. Methods: Transgender participants in the 2014 Behavioral Risk Factor Surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study of 220 patients aged 40 to 74 years, Narayan et al 32 found that transgender and nontransgender patients were equally as likely to undergo mammography, regardless of income category, higher education category, and health insurance. However, it should not be assumed that the younger generation of transgender patients would have equal levels of adherence to doctor's visits and recommendations.…”
Section: Screening Recommendationsmentioning
confidence: 99%
“…In a study of 220 patients aged 40 to 74 years, Narayan et al 32 found that transgender and nontransgender patients were equally as likely to undergo mammography, regardless of income category, higher education category, and health insurance. However, it should not be assumed that the younger generation of transgender patients would have equal levels of adherence to doctor's visits and recommendations.…”
Section: Screening Recommendationsmentioning
confidence: 99%